Shifting reasons for older men remaining uncircumcised: Findings from a pre- and post-demand creation intervention among men aged 25-39 years in western Kenya. - Kawango Agot; Jacob Onyango; George Otieno; Paul Musingila; Susan Gachau; Marylyn Ochillo; Jonathan Grund; Rachael Joseph; Edward Mboya; Spala Ohaga; Dickens Omondi; Elijah Odoyo-June (Public Library of Science (PLoS), 2024)
Voluntary medical male circumcision (VMMC) reduces men's risk of acquiring Human immunodeficiency virus (HIV) through vaginal sex. However, VMMC uptake remains lowest among Kenyan men ages 25-39 years among whom the impact on reducing population-level HIV incidence was estimated to be greatest at the start of the study in 2014. We conducted a pre- and post-intervention survey as part of a cluster randomized controlled trial to determine the effect of two interventions (interpersonal communication (IPC) and dedicated service outlets (DSO), delivered individually or together) on improving VMMC uptake among men ages 25-39 years in western Kenya between 2014 and 2016. The study had three intervention arms and a control arm. In arm one, an IPC toolkit was used to address barriers to VMMC. In arm two, men were referred to DSO that were modified to address their preferences. Arm three combined the IPC and DSO. The control arm had standard of care. At baseline, uncircumcised men ranked the top three reasons for remaining uncircumcised. An IPC demand creation toolkit was used to address the identified barriers and men were referred for VMMC at study-designated facilities. At follow-up, those who remained uncircumcised were again asked to rank the top three reasons for not getting circumcised. There was inconsistency in ranking of reported barriers at pre- and post- intervention: 'time/venue not convenient' was ranked third at baseline and seventh at follow-up; 'too busy to go for circumcision' was tenth at baseline but second at follow-up, and concern about 'what I/family will eat' was ranked first at both baseline and follow-up, but the proportion reduced from 62% to 28%. Men ages 25-39 years cited a variety of logistical and psychosocial barriers to receiving VMMC. After exposure to IPC, most of these barriers shifted while some remained the same. Additional innovative interventions to address on-going and shifting barriers may help improve VMMC uptake among older men.